International handbook on commercial arbitration (Kluwer Law International The HagueNL, 1997)
Presents national reports on arbitration law and practice, accompanied by relevant legal texts. Contains national reports on sixty countries.
At head of title: International Council for Commercial Arbitration. Companion publication to : Yearbook, commercial arbitration